Exploring the Arabic Learning Strategies at Senior High School - Ranita Sari; Renni Hasibuan; Titi Fitri; Rafid Sibah At-Tamimi (IJECA (International Journal of Education and Curriculum Application), 2024)
This research aims to reveal and describe the Arabic language learning strategies implemented at Al-Falah Senior High School Padang. This research employs a qualitative descriptive approach, The data collection methods used in this research are interview with head and two arabic taechers. Then,observation by directly observing Arabic language learning activities carried out in this Madrasah. The data analysis technique steps used in this research are: Data Collection, data collection activities in this research are by using interviews, observation and documentation. then Data Reduction, Data Presentation, Verification and confirmation of conclusions. The reseacrh findings are the Arabic learning at this school shows a comprehensive approach through combining the Merdeka and 2013 curriculum. Although various learning methods and media have been implemented, including Sam'iyyah Syafawiyyah, Qawa'id wa Tarjamah, and projectors LCD and computers, the main challenge lies in the lack of student interest, It is caused by the low relevance of the material to their needs or interests,. Learning evaluation includes assessment of attitudes, knowledge competencies, and skills, providing a holistic picture of student progress. Although efforts are made through extracurricular and special programs, in-depth evaluation of learning strategies in dormitories is crucial to increasing learning effectiveness. The implications of this research indicate the need for enhancing teaching strategies and student motivation to overcome the challenge of insufficient interest in learning Arabic at this school, By focusing on designing materials relevant to daily life and conducting ongoing evaluations of extracurricular Arabic language programs in the boarding school..